Incident Precipitation, Throughfall and Stemflow chemistry in Pinus wallichiana A.B. Jack. stand in Dal Lake catchment, Srinagar, J & K, India - Wani, M. A.; Manhas, R. K.; Singh, Yash Paul (Indian Forester, 2022)
The paper presents the results of chemical analysis of stem flow, throughfall and incident precipitation under Pinus wallichiana stand located in Dal Lake catchment in Kashmir Himalayas. The maximum values of Na (10.6 mg l -1), Cl (7.0 mg l -1) and K (2.3 mg l -1) were found in throughfall followed by stemflow (Na = 7.2 mg l -1; Cl = 4.6 mg l -1; K = 1.4 mg l - 1) and incident rainfall (Na = 4.8 mg l -1; Cl = 3.0 mg l -1; K = 1.0 mg l -1). In case of phosphorus however, the maximum values (1.5 mg l -1) were found in incident rainfall and minimum (0.8 mg l -1) in throughfall. The values of all four nutrients varied significantly (P < 0.05) during the course of the study. General trend of increase in nutrients in stemflow, throughfall and incident rainfall was in the order of Na > Cl > K > P. All four nutrients of the stemflow were significantly (P < 0.05) and positively correlated with the diameter at breast height (DBH), and inversely correlated with tree height, however this relationship was not significant. In case of throughfall, Na (r = 0.46), Cl (r = 0.60), K (r = 0.57) and P (r = 0.59) were significantly (P < 0.01) correlated with the crown area.